POLITICAL ACTIVITY IS THE BASIS OF NATIONAL DEVELOPMENT (American Journal of Research in Humanities and Social Sciences, 2023)
This scientific article states that in the first years of national independence, Uzbekistan`s profound institutional modifications in all spheres of society such as political, economic, social and spiritual conditions for the formation of civil society.